Pengaruh Pemasaran Konten Instagram Akun @Sodfestival terhadap Minat Membeli Tiket Festival Musik “Sound of Downtown” - Maharani, Ginza Putri (Journal of Management and Bussines (JOMB), 2024)
This study aims to analyze the influence of Instagram content marketing on ticket purchase interest at the Sounds of Downtown (SoD) music festival. The method used is a quantitative approach with data collection through questionnaires to 100 respondents, who are followers of the Instagram account @sodfestival aged 15-26 years. The data analysis technique uses the Pearson Product Moment correlation test, T test, and F test. The results of the study indicate that there is a positive and significant relationship between Instagram content marketing and purchase interest (r = 0.918, p <0.05). In addition, Instagram content marketing has a significant effect on purchase interest with a determination coefficient of 84.2%, indicating that this variable is able to explain most of the variation in purchase interest. The results of the T test (t = 22.864, p <0.05) and F test (F = 522.764, p <0.05) support that Instagram content marketing has a significant effect on ticket purchase interest. Thus, content marketing through Instagram has proven to be an effective strategy in increasing consumer purchase interest at the Sounds of Downtown music festival. Keywords: Engagement, Music Festival, Instagram, Online Questionnaire, Purchase Interest, Internet Users, Online Marketing Strategy